An evaluation of network management protocols - Gonçalves, Pedro
During the last decade several network management solutions have been proposed or extended to cope with the growing complexity of networks, systems and services. Architectures, protocols, and information models have been proposed as a way to better respond to the new and different demands of global networks. However this offer also leads to a growing complexity of management solutions and to an increase in systems' requirements. The current management landscape is populated with a multiplicity of protocols, initially developed as an answer to different requirements. This paper presents a comparative study of currently common management protocols in All-IP networks: SNMP, COPS, Diameter, CIM/XML over HTTP and CIM/XML over SOAP. This assessment was focused on wireless aspect issues, and as such includes measures of bandwidth, packets, round-trip delays, and agents' requirements. We also analyzed the advantages of compression in these protocols.